(untitled) (Italiano LinguaDue, 2011)
L’articolo propone alcune considerazioni sull’uso di materiali autentici nell’insegnamento/apprendimento della lingua straniera per sviluppare la comprensione orale tramite l’utilizzo di un notiziario. Partendo da una breve introduzione che sottolinea la centralità dello sviluppo dell’abilità di ascolto nell’insegnamento linguistico, seguono delle riflessioni sulle modalità di un possibile percorso didattico, con esempi di obiettivi ed attività. Dopo alcune considerazioni teoriche sulle caratteristiche di un notiziario, concludono l’articolo delle proposte di lavoro indirizzate a studenti di italiano LS. Anche non vengono nascoste le difficoltà che l’insegnante può incontrare nell’utilizzo di materiali autentici come il notiziario, viene confermata la loro importanza ed insostituibile efficacia nell’insegnamento /apprendimento della lingua straniera o seconda. The news, or the importance of using authentic materials in language teaching-learning The article deals with the use of authentic materials in foreign language acquisition. It mainly emphasizes listening comprehension supported by radio news. It starts with a short introduction that focuses on the importance of the development of listening comprehension in foreign language acquisition and goes on with reflections about the learning goals and exercises in a didactic unit. Further aspects considered are theories regarding the characteristics of a certain kinds of text like “the news”. The article concludes with suggestions for didactic activities, mainly for learners of Italian as a foreign language. On the one hand, the article does not conceal the fact that often there are difficulties for teachers when it comes to using authentic materials such radio news reports, but on the other hand, it points out and confirms the importance and effect of such materials.